Preparation and properties of fused silica ceramics by Isobam spontaneous coagulation casting. Issue 4 (15th February 2022) - Mao, Dongliang; Yin, Shuang; Fang, Xia; Wang, Yang; Li, Qvan; Yang, Jian
Abstract: By surface modification with APTMS, spontaneous coagulation casting (SCC) of fused silica based on Isobam was achieved and the possible coagulation and molding mechanism is proposed. Through the interaction between the polar groups on the Isobam molecular chain and the incorporated –NH2 groups on the surface of the silica particles, Isobam molecular chains were adsorbed on the surface of particles, which initiate the formation of flocs and the solidification of the suspension. The addition of dispersant TMAH results in the hydrolyzation of Isobam, forming more –COO –, which effectively improves the fluidity and stability of the suspension. Then the zeta potential, rheological properties and coagulation behavior of the suspension were systematically investigated and the fused silica suspension with high solid content (up to 52 vol%), low viscosity and good coagulation properties were prepared at 1.8 wt% TMAH and 0.5 wt% Isobam dosage. After sintering at 1260 °C for 4 hours, the fused silica ceramics (50 vol% solid content) shows a high bending strength of 61.59 MPa, the lowest dielectric loss tanδ of 8.46×10 -4 and the dielectric constant of 3.72. Thus, this work provides a simple and effective method for preparing fused silica and other ceramics with negative surface charge by Isobam SCC.